Safety analysis of quinolones use in minors—based on the FAERS database - Li, Yanwei; Wang, Jing; Wang, ChengLiang; Chen, Li (Frontiers in Medicine, 2024)
Objective: This study utilizes the FDA Adverse Event Reporting System (FAERS) to investigate adverse drug event (ADE) signals linked to quinolones use (ciprofloxacin, moxifloxacin, levofloxacin, ofloxacin) in minors, offering insights for clinical use.Methods: Minors were categorized into four age groups. ADE reports for these quinolones from the first quarter of 2015 to the third quarter of 2023 were extracted from the FAERS database. Data analysis used reporting odds ratio (ROR) and the MHRA method.Results: Most ADE cases in minors involved ciprofloxacin(575)and levofloxacin (477). In the infant group, various injury, poisoning, and procedural complication events were more frequently associated with ciprofloxacin, levofloxacin, and moxifloxacin (19.83%, 31.25%, and 100.00%, respectively). In the preschool children group, psychiatric disorders were more frequently reported with levofloxacin and ofloxacin use (59.00% and 47.62%, respectively). Ocular disorders were notably associated with moxifloxacin in the children group (62.50%), In the adolescent group, more gastrointestinal diseases occurred with ciprofloxacin (12.96%).: ADE occurrence with quinolones in minors varies by age. Strict adherence to indications, rational use, avoiding prolonged use, and monitoring for short-term reactions are essential. Enhanced monitoring of interactions and drug education are crucial to reducing ADE.